Psychosocial health of migrant careworkers from Southeast Asian countries in Israel: A mixed methods study - Jordan Hannink Attal; Ido Lurie; Yehuda Neumark (Elsevier, 2024)
Background: In 2018, 66,859 migrant careworkers were in Israel, most of whom originated from Southeast Asian countries and 81 % of whom are women. Stringent regulations combined with social invisibility creates vulnerabilities that may contribute to emotional distress. This study aimed to assess psychosocial status and determine mechanisms of emotional distress and resilience in this population. Methods: Mixed methods were used in this cross-section study. An online survey measured demographic variables, psychosocial wellbeing using the HSCL-25 questionnaire, general health, perceived social support, cultural identity, and perceived othering. Based on the survey's results, interviews were conducted with a subpopulation of respondents (n = 15) to further understand the mechanisms of emotional distress and resilience, and were analyzed using a postcolonial feminist framework and grounded theory. Data collection took place during 2018-2019. Results: In total, 263 careworkers completed the survey and 15 careworkers were interviewed. The overall prevalence of emotional distress according to the HSCL-25 was 36.8 %, 22.6 % on the anxiety subscale, and 41.8 % on the depression subscale. Emotional distress was associated with female sex, not being parents, poorer general health, high perceived othering, and low perceived social support. Interviews revealed that Israeli policy, and relationships with family in their country of origin and with Israeli employers and their families can either contribute to or mitigate emotional stressors. Conclusions: Symptoms of emotional distress among Southeast Asian migrant careworkers in Israel are frequently reported, and may indicate rates of anxiety and depression higher than in careworkers' countries of origin and host country. Increased monitoring to protect careworkers' rights and including mental health services as part of their health insurance plan are warranted.